An experimental investigation into multi-functional Z-pinned composite laminates. (15th October 2016) - Zhang, B.; Allegri, G.; Hallett, S.R.
Abstract: This paper investigates the feasibility of monitoring progressive delamination growth in Z-pinned composite laminates via the measurement of through-thickness electrical resistance. This novel health monitoring technique is based on connecting Z-pins both in series and in parallel by means of arrays of electrodes arranged on the laminate surfaces. This creates a multi-functional (through-thickness reinforcing and sensing) laminated structure. Experimental results on double-cantilever beam coupons demonstrate that the entire Mode I bridging response of Z-pins can be monitored, from the arrival of the delamination front to the complete pull-out of the through-thickness reinforcement. Hence the extent of delamination can be inferred from the through-thickness resistance. This is proved for both conductive (carbon fibre-reinforced) and non-conductive (glass fibre-reinforced) laminates. The premature Z-pin failure during progressive pull-out corresponds to an abrupt increase of through-thickness electrical resistance. The delamination sensing/suppression method presented in this paper can be readily applied to Z-pinned composites at structural level. Graphical abstract: Highlights: A novel method for enabling delamination sensing in Z-pinned composite laminates is proposed; Z-pins are connected in series and in parallel. The delamination-sensing method is demonstrated at coupon level through testing of double-cantilever beam specimens The delamination-sensing method presented can be readily extended to structural Z-pinned components.